2014
DOI: 10.1080/09639284.2013.875690
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Associate Partnerships: Practitioners’ Involvement in the Delivery of an Auditing Course Based on a Case-Study: A Teaching Resource

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Audit can be a difficult subject to teach, due to the practical nature of the subject, and the unfortunate pre conception by some students that "auditing really is boring" (Power, 1999, p. xii). To avoid these issues, there have been innovations in the past within the auditing module at Newcastle Business School (NBS), at the University of Northumbria, including the use of corporate associate partners (Slack, Loughran, & Abrahams, 2014), which complements the delivery of module materials by academics who have previously worked in audit practice. Case study material has also been used within classes to try to bring the subject to life further, with practical application by students using examples of audit documentation.…”
Section: Introduction and Context Of The 'Northumbria' Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Audit can be a difficult subject to teach, due to the practical nature of the subject, and the unfortunate pre conception by some students that "auditing really is boring" (Power, 1999, p. xii). To avoid these issues, there have been innovations in the past within the auditing module at Newcastle Business School (NBS), at the University of Northumbria, including the use of corporate associate partners (Slack, Loughran, & Abrahams, 2014), which complements the delivery of module materials by academics who have previously worked in audit practice. Case study material has also been used within classes to try to bring the subject to life further, with practical application by students using examples of audit documentation.…”
Section: Introduction and Context Of The 'Northumbria' Simulationmentioning
confidence: 99%
“…The previous initiative of using corporate partners included visiting seminar activities from a local firm (Ryecroft Glenton) who carried out a number of tasks with students, based on the case of a multinational client (Slack, Loughran & Abrahams, 2014;Sanchez, Agoglia & Brown, 2012). The implications of these initiatives, however, included cost, timetabling and resourcing implications (which the practitioners dictated) and in some cases students became critical of the visiting practitioners (with comments including 'they are not proper teachers').…”
Section: Introduction and Context Of The 'Northumbria' Simulationmentioning
confidence: 99%
“…Studies have identified that effort may be afforded to trying to promote better use of skills as well as the development of new skills; however, if students do not engage fully in the activity, it is deemed useless. Past experience has found (Slack et al, 2014) that unless the students perceive some reward, engagement and satisfaction remain low. However, from an analysis of trends in accounting education literature from 1997 to 2016 by Apostolou, Dominey, Hassell and Rebele (2017), it was identified that the increased research on formative assessment, such as that undertaken by Curtis (2011) and Perera, Nguyen and Watty (2014), and further developed as a student self-assessment by Taras (2015), shows that it does aid achievement of learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Ingram and Howard (1998) examined course objectives and grading methods in introductory accounting courses and ascertained that exams were not measuring the achievement of modular learning objectives. Formative assessment can be used to help; however, Slack, Loughran and Abrahams (2014) found that unless the student perceives some reward, engagement and satisfaction remains low. In Murdoch's 2015 study, students reported that this type of learning and assessment style, i.e.…”
Section: Assessment For Future Learningmentioning
confidence: 99%
“…Collaboration where experts from different companies and organisations are invited to discuss issues with students can function as an additional teaching resource and as a way to include specialist areas in an educational course. This is something which takes place in the area of accountancy, where there is often a lack of academic teachers available to teach certain specialist areas [23,24].…”
Section: Collaboration For Improved Educationmentioning
confidence: 99%